Crystal structures of drug-metabolizing P450 monooxygenases - Johnson, Eric (Henry Stewart Talks, 2007)
Introduction to CYP450 architecture, Shared structural features, Catalytic mechanism, Redox partner interactions, Membrane topology, Multiple modes of substrate binding and oxidation
Archived at 2016/11/17